Teaching English Strategy for Young Learners - Nur Ridha; Bahrani Bahrani; Anis Komariah (Institut Agama Islam Negeri (IAIN) Manado, 2022)
AbstractTeaching English Strategy for young learners. In teaching and learning, teacher must have strategies in every subject including English lessons, the teacher must have strategies in teaching to support the learning process and achieve learning goals especially for young learners because they have different characteristics from adults, she must have strategies suitable for young learners. This research aimed to find out the strategies of teaching English to young learners at MIN 2 Kutai Kartanegara. The research design was descriptive qualitative. The subject of this research is an English teacher at MIN 2 Kutai Kartanegara. The data were obtained from interviews and documentation. Then, the data were analyzed using an interactive model of Miles, Huberman, and Saldana condensation. The technique of data validity uses triangulation data. Based on the data results, this research can be concluded that the teacher’s strategies for teaching English to young learners at MIN 2 Kutai Kartanegara were teaching planning, implementation of strategy, and teaching Evaluation. The teacher prepares the lesson plan, materials, media, and methods in teaching planning. Moreover, she implemented teaching English strategies by using demonstration, choral drill, look-and-say, pictorial illustration, verbal illustration, association, question and answer, narration, and read-and-say. She also evaluated teaching English through formative and summative evaluation.Keywords: Teaching English, Strategy, Young Learners.